2013
DOI: 10.3390/v5020758
|View full text |Cite
|
Sign up to set email alerts
|

Localization, Concentration, and Transmission Efficiency of Banana bunchy top virus in Four Asexual Lineages of Pentalonia aphids

Abstract: Banana bunchy top virus (BBTV) is the most destructive pathogenic virus of banana plants worldwide. The virus is transmitted in a circulative non-propagative manner by the banana aphid, Pentalonia nigronervosa Coquerel. In this work, we examined the localization, accumulation, and transmission efficiency of BBTV in four laboratory-established lineages of Pentalonia aphids derived from four different host plants: taro (Colocasia esculenta), heliconia (Heliconia spp.), red ginger (Alpinia purpurata), and banana … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 42 publications
1
30
0
5
Order By: Relevance
“…Pentalonia nigronervosa is the most important pest on banana and known as vector of Banana bunchy top virus (BBTV). This species plays an important role on the spread of banana bunchy top disease (Dale, 1987;Hu et al, 1996;Watanabe et al, 2013). Infection of BBTV has been reported on various banana genotypes in the world and resulted in 100% yield losses (Dale, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Pentalonia nigronervosa is the most important pest on banana and known as vector of Banana bunchy top virus (BBTV). This species plays an important role on the spread of banana bunchy top disease (Dale, 1987;Hu et al, 1996;Watanabe et al, 2013). Infection of BBTV has been reported on various banana genotypes in the world and resulted in 100% yield losses (Dale, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Even though good correlation existed among the analyzed plants and disease symptoms, one plant in each showed deviation, which may be due to experimental error. Previous reports in BBTV DNA quantification also showed real time PCR as an effective and simple method for quantification of viral load [5,8]. The results showed that the symptomatic plants harboured more viral load which was the reason for symptom expression.…”
Section: Viral Titre In Asymptomatic and Symptomatic Bbtv Infected Plmentioning
confidence: 77%
“…The Asian group comprises of the isolates from the Philippines, Taiwan, China, Japan, Indonesia, and Vietnam. The South Pacific group includes India, Pakistan, Egypt, Australia, Burundi, Tonga, Myanmar, Fiji, and USA-Hawaii and isolates from Africa [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A colony of banana aphids, which was established from an individual aphid, was maintained on healthy potted banana plants. Aphid colonies were identified as P. nigronervosa using microsatellite markers (Watanabe et al ., ).…”
Section: Methodsmentioning
confidence: 97%